PENGARUH SUBSTITUSI RUMPUT GAJAH (Pennisetum purpureum) DENGAN PELEPAH DAUN SAWIT TERHADAP KECERNAAN PROTEIN KASAR DAN KECERNAAN SERAT KASAR PADA KAMBING - Erma Rustiyana; Liman ,; Farida Fathul (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of this research was to determine effect substitution of elephant grass with palm leave sheat fermented and unfermented feed on the digestibility of crude protein and crude fiber in goats. The research lasted from October to November 2015 in Animal Husbandry Departments, Faculty of Agriculture, University of Lampung. The research used a Randomize Complete Block Design. The group based on the body weight of goats. The group amount in 3 and each group contained 3 goats, an average body weight 9–21 kg/head. Treatments : R1 (80% concentrate + 20% elephant grass); R2 (80% concentrate + 20% unfermented palm leave sheat); and R3 (80% concentrate + 20% fermented palm leave sheat). The data obtained were analyzed using ANOVA. This was followed by Duncan Test. The results showed that the substitution of elephant grass with palm leave sheat not significant (P> 0.05) on the digestibility of crude protein, but it was highly significant (P <0.01) the digestibility of crude fiber. Keywords: Goats, Palm Leave Sheat, Crude Protein Digestibility, Digestibility of Crude Fiber.